Effect of the shampoo Ultra Clean on drug concentrations in human hair - Röhrich, Jörg; Zörntlein, S.; Pötsch-Schneider, Lucia Edeltraud; Skopp, Gisela; Becker, J. (International journal of legal medicine, 2000)
The influence of the special shampoo Ultra Clean (Zydot Unlimited, Tulsa, Oklahoma) on the results of hair analyses was investigated. Hair samples from persons (n = 14) with a known history of drug abuse were collected at autopsy. The hair samples were divided into separate strands which were analyzed both after washing with Ultra Clean and without treatment. Hair analyses were performed by methanol extraction under sonication, purification by solid phase extraction and GC/MS in SIM mode according to routine procedures for tetrahydrocannabinol (THC), cocaine, amphetamine, methylenedioxyamphetamine (MDA), methylenedioxymethamphetamine (MDMA), methylenedioxyethylamphetamine (MDE), heroin, 6-monoacetylmorphine (6-MAM), morphine, codeine, dihydrocodeine and methadone. All drugs originally present in the hair fibers were still detected after a single ¶application of Ultra Clean. However, a slight decrease in drug concentrations could mostly be observed e.g. cocaine (n = 10) -5%, 6-MAM (n = 12) -9%, morphine (n = 12) -26%, THC (n = 4) -36%. The findings clearly demonstrated that drug substances had not been sufficiently removed from human hair by a single Ultra Clean treatment to drop their concentrations below the limit of detection of the analytical method applied.
Gesehen am 27.04.2021